(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
On the base of field geological-petrographycal and microscopic investigations in the Pkhrut-Lernadzor ore field the uranium bearing widespread formation of the secondary quartzite have been carried out.